A puncture-resistant rubber material and its preparation method and application

By adopting the rubber material formula containing the rare earth material LaFCS and a specific preparation process, the problem of difficult to take into account the strength and flexibility of existing puncture-resistant rubber materials is solved, and efficient puncture resistance and good wearing comfort are achieved, which is suitable for a variety of practical applications.

CN119039673BActive Publication Date: 2025-03-14TIANJIN BAOGANG RES INST OF RARE EARTHS CO LTD

Patent Information

Application Number
CN202411556219.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-03-14
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

While maintaining flexibility, existing puncture-resistant rubber materials are difficult to have sufficient strength to resist puncture, and their preparation process is complex, costly, and difficult to maintain a long-term protective effect in practical applications.

Method used

A rubber material formula containing natural rubber, petroleum-based aromatic hydrocarbons, rare earth material LaFCS water-based slurry and tributyl citrate is used, and a rubber material with good puncture resistance and flexibility is formed through a specific preparation process, including the preparation of rare earth material LaFCS and the mixing process of rubber material.

Benefits of technology

The rubber material has achieved a balance between puncture resistance and flexibility, providing excellent protection, while maintaining good breathability and wearing comfort, and is suitable for construction site anti-puncture rubber, cleaning gloves and medical gloves and other applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119039673B_ABST
    Figure CN119039673B_ABST
Patent Text Reader

Abstract

The invention provides a puncture-resistant rubber material, which comprises, by weight, 800-1200 parts of natural rubber, 80-120 parts of petroleum-based aromatic hydrocarbons, 80-120 parts of LaFCS aqueous slurry, and 20-40 parts of tributyl citrate; wherein the LaFCS aqueous slurry is obtained by mixing a rare earth material LaFCS, water, and an aqueous dispersant, and the rare earth material LaFCS is composited with raw materials including a lanthanum-containing compound, carbon black, and a copper compound, and can effectively improve the puncture resistance of the rubber material, and is expected to be applied to the preparation of rubber material products in scenes such as clinical medicine and industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of materials, and in particular relates to a puncture-resistant rubber material and a preparation method and application thereof. Background Art

[0002] The material properties of puncture-resistant rubber materials mainly include high strength, high toughness and excellent anti-puncture performance. In order to achieve these characteristics, it is necessary to select polymer materials in the preparation process, and through specific formulations and processing technologies, the rubber materials should have sufficient strength to resist puncture while maintaining flexibility. This has always been the pain point and difficulty in the research and development of puncture-resistant rubber materials. In addition, the preparation of puncture-resistant rubber materials also needs to consider factors such as wear resistance, weather resistance and environmental adaptability to ensure that they can play a lasting and stable protective role in practical applications. In the field of puncture-resistant rubber materials, there has been rapid development in recent years, and significant progress has been made in material formulation and preparation technology. However, the development of puncture-resistant rubber materials also faces challenges. The technical threshold of puncture-resistant rubber materials is high, and companies need to continue to try emerging materials in research and development, production, etc., and screen them layer by layer from the aspects of cost, performance, preparation process, etc., which is a huge project. Summary of the invention

[0003] In view of this, the present invention aims to provide a puncture-resistant rubber material and a preparation method and application thereof to solve the above-mentioned problems.

[0004] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0005] A puncture-resistant rubber material comprises, by weight, 800-1200 parts of natural rubber, 80-120 parts of petroleum-based aromatic hydrocarbons, 80-120 parts of LaFCS aqueous slurry, and 20-40 parts of tributyl citrate; wherein the LaFCS aqueous slurry is obtained by mixing a rare earth material LaFCS, water, and an aqueous dispersant; the rare earth material LaFCS comprises a lanthanum-containing compound, carbon black, and a copper compound; the lanthanum-containing compound and the carbon black are first mixed in a mass ratio of 1:1 to prepare a lanthanum-carbon mixture; then, 3-9 parts by weight of the lanthanum-carbon mixture and 1-3 parts by weight of the copper compound are mixed and poured into a sodium hydroxide solution; after reaction, the mixture is washed, dried, and calcined to obtain the puncture-resistant rubber material.

[0006] Furthermore, the lanthanum-containing compound and carbon black are mixed and fused at a high temperature of 120-150° C. for 2-4 hours to prepare a lanthanum-carbon mixture.

[0007] Furthermore, the mass concentration of the sodium hydroxide solution is 1-10%, and the usage amount is 200-400 parts by weight.

[0008] Furthermore, the reaction conditions of the lanthanum-containing compound, carbon black and sodium hydroxide solution are as follows: reacting at 80-130° C. for 3-6 hours in a hydrothermal reactor.

[0009] Further, the washing method is: washing with pure water and ethanol 3-6 times respectively;

[0010] The calcination conditions are: 800-1200°C for 4-8 hours.

[0011] Furthermore, the lanthanum-containing compound is one or more of lanthanum sulfate, lanthanum hydroxide, lanthanum nitrate, lanthanum carbonate, lanthanum oxide and hydrates thereof.

[0012] Furthermore, the copper compound is copper chloride and / or copper sulfate.

[0013] The present invention also provides a method for preparing the puncture-resistant rubber material as described above, the method comprising the following steps:

[0014] 1) Preparation of rare earth material LaFCS

[0015] First, a lanthanum-containing compound and carbon black are mixed in a mass ratio of 1:1 to prepare a lanthanum-carbon mixture, and then 3-9 parts by weight of the lanthanum-carbon mixture is mixed with 1-3 parts by weight of a copper compound and poured into a sodium hydroxide solution. After the reaction, the mixture is washed, dried, and calcined to obtain a rare earth material LaFCS;

[0016] 2) adding the obtained rare earth material LaFCS into water and an aqueous dispersant, mixing them evenly and then putting them into a sand mill for sand grinding to obtain a LaFCS aqueous slurry;

[0017] 3) Natural rubber, petroleum-based aromatic hydrocarbons, LaFCS aqueous slurry, and tributyl citrate are mixed in proportion to form a rubber mixture, and then the rubber mixture is put into a mixer for mixing so that various compounding ingredients are evenly dispersed in the rubber to form a rubber material.

[0018] Furthermore, in step 2), the addition mass ratio of the rare earth material LaFCS, water, and aqueous dispersant is 10:90:1, the sand milling time is 4-8 hours, and the particle size after grinding is 400-800 nm.

[0019] The present invention also provides a use of the puncture-resistant rubber material as described above in puncture-resistant rubber leather, cleaning gloves, and medical gloves for construction sites.

[0020] Compared with the prior art, the puncture-resistant rubber material and the preparation method thereof of the present invention have the following advantages:

[0021] The rare earth material LaFCS described in the present invention has a very good unloading effect due to its unique lamellar structure and mechanical properties. When the material is added to the production process of rubber in the form of an additive, the lamellar structure can be effectively integrated with the soft fabric bottom layer, achieving the rigidity and flexibility of the rubber, not only providing excellent protective performance, but also ensuring flexibility when worn. Moreover, due to the particularity of the lamellar structure, even while increasing the protectiveness, it can also maintain good air permeability, which is very important for users who wear gloves for a long time, and can effectively reduce hand sweating and discomfort. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0023] Figure 1 It is the particle size test data of LaFCS-1 water-based slurry;

[0024] Figure 2 This is the SEM scanning electron microscope image of LaFCS-1 water-based slurry;

[0025] Figure 3 To detect the thickness of each rubber;

[0026] Figure 4 The puncture force required to puncture each rubber. DETAILED DESCRIPTION

[0027] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1 Preparation of puncture-resistant rubber material

[0030] The preparation method comprises the following steps:

[0031] 1) Preparation of rare earth material LaFCS

[0032] 100 g of lanthanum oxide and 100 g of carbon black were mixed and put into a reactor, and the reactor was placed in an oven at 140° C. for 3 hours to prepare a lanthanum-carbon mixture.

[0033] Then, 50 g of the lanthanum-carbon mixture was mixed with 20 g of copper sulfate, and slowly added into 3000 mL of 5% sodium hydroxide aqueous solution. After stirring for 45 min, the mixture was transferred to a hydrothermal kettle and reacted at 110 ° C for 4 hours. The mixture was filtered and washed with pure water and ethanol for 3 times, dried at 70 ° C for 4 hours, and then placed in a muffle furnace and calcined at 900 ° C for 6 hours to obtain the rare earth material LaFCS-1.

[0034] 2) adding the obtained rare earth material LaFCS-1 into water and an aqueous dispersant, mixing them evenly and then putting them into a sand mill for sand grinding to obtain a LaFCS-1 aqueous slurry;

[0035] Among them, the added mass ratio of rare earth material LaFCS-1, water, and aqueous dispersant is: 10:90:1, the sand grinding time is 6 hours, and the particle size after grinding is 487nm.

[0036] 3) 1000 g of natural rubber, 100 g of petroleum-based aromatic hydrocarbons, 100 g of LaFCS-1 aqueous slurry, and 30 g of tributyl citrate were mixed to prepare a rubber mixture, and then the rubber mixture was put into a mixer and the mixing temperature was set to 180°C. The mixture was mixed for 3 hours to allow various compounding ingredients to be evenly dispersed in the rubber to form a rubber material. The prepared rubber material was kept at 180°C and was made into a puncture-resistant rubber product, rubber skin XJ1, through a special mold and molding process.

[0037] The particle size of the LaFCS-1 aqueous slurry was tested. The experimental results are as follows: Figure 1 As shown in the figure, the particle size of the material is small after sand grinding. The slurry is scanned by SEM electron microscope, and the experimental results are as follows Figure 2 As shown, the material has a unique lamellar structure and mechanical properties, which makes the material itself have a very good force-unloading effect. Adding the material in the preparation process of the rubber can effectively improve the anti-puncture ability of the rubber product.

[0038] Example 2 Preparation of puncture-resistant rubber material

[0039] The preparation method comprises the following steps:

[0040] 1) Preparation of rare earth material LaFCS

[0041] 100 g of lanthanum oxide and 100 g of carbon black were mixed and put into a reactor, and the reactor was placed in an oven at 150° C. for 2 hours to prepare a lanthanum-carbon mixture.

[0042] Then, 90 g of the lanthanum-carbon mixture was mixed with 30 g of copper sulfate, and slowly added into 4000 mL of 8% sodium hydroxide aqueous solution. After stirring for 45 min, the mixture was transferred to a hydrothermal kettle and reacted at 130 ° C for 4 hours. The mixture was filtered and washed with pure water and ethanol for 3 times, dried at 70 ° C for 4 hours, and then placed in a muffle furnace and calcined at 1000 ° C for 7 hours to obtain the rare earth material LaFCS-2.

[0043] 2) adding the obtained rare earth material LaFCS-2 into water and an aqueous dispersant, mixing them evenly and then putting them into a sand mill for sand grinding to obtain a LaFCS-2 aqueous slurry;

[0044] Among them, the added mass ratio of rare earth material LaFCS-2, water, and aqueous dispersant is: 10:90:1, the sand grinding time is 6 hours, and the particle size after grinding is 567nm.

[0045] 3) 900 g of natural rubber, 90 g of petroleum-based aromatic hydrocarbons, 90 g of LaFCS-2 aqueous slurry, and 30 g of tributyl citrate were mixed to form a rubber mixture, and then the rubber mixture was put into a mixer and the mixing temperature was set to 180°C. The mixture was mixed for 3 hours to allow various compounding ingredients to be evenly dispersed in the rubber to form a rubber material. The prepared rubber material was kept at 180°C and was made into a puncture-resistant rubber product, rubber skin XJ2, through a special mold and molding process.

[0046] Example 3 Preparation of puncture-resistant rubber material

[0047] The preparation method comprises the following steps:

[0048] 1) Preparation of rare earth material LaFCS

[0049] 100 g of lanthanum sulfate and 100 g of carbon black were mixed and put into a reactor, and the reactor was placed in an oven at 130° C. for 4 hours to prepare a lanthanum-carbon mixture.

[0050] Then, 30 g of the lanthanum-carbon mixture was mixed with 10 g of copper chloride, and slowly added into 2000 mL of 3% sodium hydroxide aqueous solution. After stirring for 45 min, the mixture was transferred to a hydrothermal kettle and reacted at 90 ° C for 4 hours. The mixture was filtered and washed with pure water and ethanol for 3 times, dried at 70 ° C for 4 hours, and then placed in a muffle furnace and calcined at 1200 ° C for 4 hours to obtain the rare earth material LaFCS-3.

[0051] 2) adding the obtained rare earth material LaFCS-3 into water and an aqueous dispersant, mixing them evenly and then putting them into a sand mill for sand grinding to obtain a LaFCS-3 aqueous slurry;

[0052] Among them, the added mass ratio of rare earth material LaFCS-3, water, and aqueous dispersant is: 10:90:1, the sand grinding time is 6 hours, and the particle size after grinding is 543nm.

[0053] 3) 1200 g of natural rubber, 90 g of petroleum-based aromatic hydrocarbons, 90 g of LaFCS-3 aqueous slurry, and 30 g of tributyl citrate were mixed to form a rubber mixture, and then the rubber mixture was put into a mixer and the mixing temperature was set to 180°C. The mixture was mixed for 3 hours to allow various compounding ingredients to be evenly dispersed in the rubber to form a rubber material. The prepared rubber material was kept at 180°C and was made into a puncture-resistant rubber product, rubber skin XJ3, through a special mold and molding process.

[0054] Comparative Example 1

[0055] The difference from Example 3 is that the addition ratio of the lanthanum-carbon mixture and the copper compound is different, as follows:

[0056] Mix 100 g of lanthanum-carbon mixture with 10 g of copper chloride, slowly add into 2000 mL of 3% sodium hydroxide aqueous solution, stir for 45 min, transfer to a hydrothermal kettle, react at 90 °C for 4 hours, filter and wash with pure water and ethanol three times respectively, dry at 70 °C for 4 hours, put into a muffle furnace and set at 1200 °C for calcination for 4 hours to obtain the rare earth material LaFCS-4.

[0057] The other steps are the same as those in Example 3, and finally the puncture-resistant rubber product rubber skin XJ4 is manufactured.

[0058] Comparative Example 2

[0059] The difference from Example 3 is that the addition ratio of the lanthanum-carbon mixture and the copper compound is different, as follows:

[0060] Mix 10 g of lanthanum-carbon mixture with 100 g of copper chloride, slowly add into 2000 mL of 3% sodium hydroxide aqueous solution, stir for 45 min, transfer to a hydrothermal kettle, react at 90 °C for 4 hours, filter and wash with pure water and ethanol three times respectively, dry at 70 °C for 4 hours, put into a muffle furnace and set at 1200 °C for calcination for 4 hours to obtain the rare earth material LaFCS-5.

[0061] The other steps are the same as those in Example 3, and finally the puncture-resistant rubber product leather XJ5 is manufactured.

[0062] Comparative Example 3

[0063] The difference from Example 3 is that the concentration of the sodium hydroxide solution is different, specifically as follows:

[0064] Mix 30 g of lanthanum carbon mixture with 10 g of copper chloride, slowly add into 2000 mL of 15% sodium hydroxide aqueous solution, stir for 45 min, transfer to a hydrothermal kettle, react at 90 °C for 4 hours, filter and wash with pure water and ethanol three times respectively, dry at 70 °C for 4 hours, put into a muffle furnace and set at 1200 °C for 4 hours to obtain the rare earth material LaFCS-6.

[0065] The other steps are the same as those in Example 3, and finally the puncture-resistant rubber product rubber skin XJ6 is manufactured.

[0066] Comparative Example 4

[0067] The difference from Example 1 is that the reaction conditions of the hydrothermal reactor are different, as follows:

[0068] Mix 50 g of lanthanum-carbon mixture with 20 g of copper sulfate, slowly add into 3000 mL of 5% sodium hydroxide aqueous solution, stir for 45 min, transfer to a hydrothermal kettle, react at 60 °C for 4 hours, filter and wash with pure water and ethanol three times respectively, dry at 70 °C for 4 hours, put into a muffle furnace and set at 900 °C for calcination for 6 hours to obtain the rare earth material LaFCS-7.

[0069] The other steps are the same as those in Example 1, and finally the puncture-resistant rubber product leather XJ7 is manufactured.

[0070] Comparative Example 5

[0071] The difference from Example 1 is that no washing is performed, as follows:

[0072] Mix 50 g of lanthanum-carbon mixture with 20 g of copper sulfate, slowly add into 3000 mL of 5% sodium hydroxide aqueous solution, stir for 45 min, transfer to a hydrothermal kettle, react at 110 °C for 4 hours, filter and wash without pure water and ethanol, dry at 70 °C for 4 hours, put into a muffle furnace and set at 900 °C for calcination for 6 hours to obtain the rare earth material LaFCS-8.

[0073] The other steps are the same as those in Example 1, and finally the puncture-resistant rubber product leather XJ8 is manufactured.

[0074] Comparative Example 6

[0075] The difference from Example 1 is that the calcination temperature is different, as follows:

[0076] Mix 50 g of lanthanum-carbon mixture with 20 g of copper sulfate, slowly add into 3000 mL of 5% sodium hydroxide aqueous solution, stir for 45 min, transfer to a hydrothermal kettle, react at 110 °C for 4 hours, filter and wash with pure water and ethanol three times respectively, dry at 70 °C for 4 hours, put into a muffle furnace and set at 1500 °C for calcination for 6 hours to obtain the rare earth material LaFCS-9.

[0077] The other steps are the same as those in Example 1, and finally the puncture-resistant rubber product rubber skin XJ9 is manufactured.

[0078] Comparative Example 7

[0079] The difference from Example 1 is that the ratio of the lanthanum compound to the carbon black in the lanthanum-carbon mixture is different, as follows:

[0080] Take 10g of lanthanum oxide and 100g of carbon black, mix them and put them into a reactor. Put the reactor into an oven, set the temperature to 140°C and react and fuse for 3 hours to make a lanthanum-carbon mixture.

[0081] Mix 50 g of lanthanum-carbon mixture with 20 g of copper sulfate, slowly add into 3000 mL of 5% sodium hydroxide aqueous solution, stir for 45 min, transfer to a hydrothermal kettle, react at 110 °C for 4 hours, filter and wash with pure water and ethanol three times respectively, dry at 70 °C for 4 hours, put into a muffle furnace and set at 900 °C for calcination for 6 hours to obtain the rare earth material LaFCS-10.

[0082] The other steps are the same as those in Example 1, and finally the puncture-resistant rubber product leather XJ10 is manufactured.

[0083] Comparative Example 8

[0084] The difference from Example 1 is that the reaction conditions of the lanthanum-carbon mixture are different, specifically as follows:

[0085] Take 100g of lanthanum oxide and 100g of carbon black, mix them and put them into a reactor. Put the reactor into an oven, set the temperature to 80°C and react and fuse for 6 hours to make a lanthanum-carbon mixture.

[0086] Mix 50 g of lanthanum-carbon mixture with 20 g of copper sulfate, slowly add into 3000 mL of 5% sodium hydroxide aqueous solution, stir for 45 min, transfer to a hydrothermal kettle, react at 110 °C for 4 hours, filter and wash with pure water and ethanol three times, dry at 70 °C for 4 hours, put into a muffle furnace and set at 900 °C for calcination for 6 hours to obtain the rare earth material LaFCS-11.

[0087] The other steps are the same as those in Example 1, and finally the puncture-resistant rubber product leather XJ11 is manufactured.

[0088] Comparative Example 9

[0089] The difference from Example 1 is that lanthanum is replaced with other materials, as follows:

[0090] 100 g of silicon dioxide and 100 g of carbon black were mixed and put into a reactor, and the reactor was put into an oven, and the temperature was set to 130° C. for 4 hours to react and fuse to prepare a silicon-carbon mixture;

[0091] Mix 50 g of silicon-carbon mixture with 20 g of copper sulfate, slowly add into 3000 mL of 5% sodium hydroxide aqueous solution, stir for 45 min, transfer to a hydrothermal kettle, react at 110 °C for 4 hours, filter and wash with pure water and ethanol three times respectively, dry at 70 °C for 4 hours, put into a muffle furnace and set at 900 °C for calcination for 6 hours to obtain the rare earth material LaFCS-12.

[0092] The other steps are the same as those in Example 1, and finally the puncture-resistant rubber product rubber skin XJ12 is manufactured.

[0093] Comparative Example 10

[0094] The difference from Example 1 is that carbon black is replaced with graphene, as follows:

[0095] 100 g of lanthanum oxide and 100 g of graphene were mixed and put into a reactor, and the reactor was put into an oven, and the temperature was set to 130° C. for 4 hours to react and fuse to prepare a lanthanum-carbon mixture;

[0096] Mix 50 g of lanthanum-carbon mixture with 20 g of copper sulfate, slowly add into 3000 mL of 5% sodium hydroxide aqueous solution, stir for 45 min, transfer to a hydrothermal kettle, react at 110 °C for 4 hours, filter and wash with pure water and ethanol three times respectively, dry at 70 °C for 4 hours, put into a muffle furnace and set at 900 °C for calcination for 6 hours to obtain the rare earth material LaFCS-13.

[0097] The other steps are the same as those in Example 1, and finally the puncture-resistant rubber product rubber skin XJ13 is manufactured.

[0098] Experiment: Comparison of puncture resistance

[0099] The puncture resistance performance of puncture-resistant rubber materials is its core evaluation index.

[0100] At present, the puncture resistance performance test methods for puncture-resistant rubber materials mainly include mechanical puncture tests and puncture tests simulating actual working environments. Through these test methods, the puncture resistance performance of puncture-resistant rubber materials can be comprehensively evaluated, providing a scientific basis for their application in different fields.

[0101] The specific detection method is: first, the rubber made of ordinary rubber material without rare earth filler (control group) and the rubber made of puncture-resistant rubber material with rare earth filler (experimental group) are cut or prepared according to the specified size and shape to ensure the integrity and consistency of the samples. At the same time, the samples are properly cleaned and treated to eliminate the influence of surface contamination and impurities on the test results. According to the test standards and sample characteristics, puncture test equipment with high precision and stability is selected to ensure that the parameters of the equipment are set correctly, such as puncture speed, force, etc., to meet the test requirements. Then install the fixture correctly according to the equipment manual to ensure that it is stable and reliable. Place the processed sample in the fixture, and adjust the position and angle of the fixture so that the sample is in the correct position and state during the test. After confirming that the sample is clamped and positioned correctly, start the puncture test. According to the requirements of the test standard, control the puncture speed, force and other parameters, set up 3 parallel groups for each experimental group, and finally record the average test results. The experimental results are as follows Figure 3 , Figure 4 As shown:

[0102] We first tested the blank control rubber without rare earth additives. After setting up three parallel groups and taking the average, we found that the thickness of the blank control rubber was 0.126mm and the puncture force was 2.14N.

[0103] Thickness, such as Figure 3 As shown in the figure, after adding different rare earth fillers LaFCS, the thickness of the rubber changed differently. First, the thickness of XJ1-3 increased by less than 0.01mm, and the thickness change was not large. However, XJ4-13 increased by about 0.03. This is because the synthesis process of XJ4-13 is incorrect, resulting in an imperfect sheet structure of the material, so the thickness of the rubber will be greatly affected when added in the process, especially XJ8. The rare earth material has not been washed, resulting in more impurities, and the thickness of the rubber produced in the end increased significantly.

[0104] In terms of puncture force, Figure 4 As shown in the figure, the puncture resistance of XJ1-3 is significantly improved, more than 2 times that of the blank control. The puncture resistance of XJ4-13 is also improved, but the improvement effect is worse than that of XJ1-3. On the one hand, it is due to the addition of rare earth materials as additives. After all, there is one more ingredient, which will increase some puncture resistance. On the other hand, the increase in the thickness of the rubber will also bring some puncture resistance. However, considering all factors, XJ1-3 still has the best puncture resistance. It does not change the thickness of the rubber, maintains the sensitivity of the rubber, and increases the puncture resistance of the rubber. In practical applications, it can improve the protection effect of operators.

[0105] In addition, through the comparison of the above comparative examples, it can be seen that the puncture resistance of the puncture-resistant rubber material is related to the composition and proportion of the rare earth filler, and is also related to the preparation conditions of the rare earth material LaFCS. Only by preparing the rare earth material LaFCS according to the scheme given in this application can the puncture resistance of the rubber material be better improved.

[0106] In summary, the rare earth filler LaFCS material is non-toxic and healthy, and the preparation process is green and environmentally friendly. Adding rare earth filler LaFCS in the rubber production process can improve the rubber's anti-puncture ability. With the continuous optimization of preparation technology and filling methods, the performance of puncture-resistant rubber will continue to improve and will be able to meet the needs of more fields.

[0107] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A puncture-resistant rubber material, characterized in that: The composition comprises 800-1200 parts of natural rubber, 80-120 parts of petroleum-based aromatic hydrocarbons, 80-120 parts of LaFCS aqueous slurry, and 20-40 parts of tributyl citrate by weight; wherein the LaFCS aqueous slurry is obtained by mixing rare earth material LaFCS, water, and an aqueous dispersant; the rare earth material LaFCS comprises a lanthanum-containing compound, carbon black, and a copper compound; the lanthanum-containing compound and the carbon black are first mixed in a mass ratio of 1:1 to prepare a lanthanum-carbon mixture; then 3-9 parts by weight of the lanthanum-carbon mixture are mixed with 1-3 parts by weight of the copper compound, and then poured into a sodium hydroxide solution; after the reaction, the mixture is washed, dried, and calcined to obtain the mixture; The mass concentration of the sodium hydroxide solution is 1-10%, and the usage amount is 200-400 parts by weight; The reaction conditions of the lanthanum-containing compound, carbon black and sodium hydroxide solution are as follows: in a hydrothermal reactor, react at 80-130° C. for 3-6 hours; Wash with pure water and ethanol 3-6 times respectively; Calcination conditions: 800-1200°C for 4-8 hours; The lanthanum-containing compound is one or more of lanthanum sulfate, lanthanum hydroxide, lanthanum nitrate, lanthanum carbonate, lanthanum oxide and hydrates thereof.

2. The puncture-resistant rubber material according to claim 1, characterized in that: The lanthanum-containing compound and carbon black are mixed and fused at a high temperature of 120-150° C. for 2-4 hours to prepare a lanthanum-carbon mixture.

3. The puncture-resistant rubber material according to claim 1, characterized in that: The copper compound is copper chloride and / or copper sulfate.

4. A method for preparing a puncture-resistant rubber material according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: 1) Preparation of rare earth material LaFCS First, a lanthanum-containing compound and carbon black are mixed in a mass ratio of 1:1 to prepare a lanthanum-carbon mixture, and then 3-9 parts by weight of the lanthanum-carbon mixture is mixed with 1-3 parts by weight of a copper compound and poured into a sodium hydroxide solution. After the reaction, the mixture is washed, dried, and calcined to obtain a rare earth material LaFCS; 2) adding the obtained rare earth material LaFCS into water and an aqueous dispersant, mixing them evenly and then putting them into a sand mill for sand grinding to obtain a LaFCS aqueous slurry; 3) Natural rubber, petroleum-based aromatic hydrocarbons, LaFCS aqueous slurry, and tributyl citrate are mixed in proportion to form a rubber mixture, and then the rubber mixture is put into a mixer for mixing so that various compounding ingredients are evenly dispersed in the rubber to form a rubber material.

5. The method for preparing the puncture-resistant rubber material according to claim 4, characterized in that: Step 2) The mass ratio of the rare earth material LaFCS, water and aqueous dispersant added is 10:90:1, the sand grinding time is 4-8 hours, and the particle size after grinding is 400-800nm.

6. Use of the puncture-resistant rubber material according to any one of claims 1 to 3 in puncture-resistant rubber gloves, cleaning gloves, and medical gloves at construction sites.

Citation Information

Patent Citations

  • Rare-earth-based infrared heating thermal fabric as well as preparation method and application thereof

    CN114541138A

  • Method for preparing modified rubber, modified rubber, and bulletproof and puncture resistant tire

    US20200114685A1

Cited By

  • Carbon-carbon composite 3D printing material and preparation method thereof

    CN121575513A